Alimentación saludable y política pública, análisis de caso; Colegio Fiscal El Empalme, año 2012-2014 - Vásquez Salvatierra, Elsy Fátima (2015)
This research was developed in the Educational Unit The Empalme, the same is located at Av. Quevedo, Km. 11/2, in the city the Laureles, El Empalme city province of Los Rios. The development began with the introduction, whose overall objective is: To analyze the relationship of public policy with the system of school feeding in El Empalme Education Unit; specific objective) Diagnose the current situation on the handling and storage of food in the bars of the institution, b) Investigate the implementation of public policy for existing bars in the Education Unit The Empalme, c) Design a food guide procedures the bars of the Education Unit The Empalme applied to current public policy. Theoretical and legal foundations necessary for the study cited, location and duration of the investigation was determined, the materials and equipment used in research are described, as well the type of research was determined, methods, sources of research, technical and assessment tools, the student population of the Education Unit the Empalme screened, 337 surveys applied an interview Mr. Rector of the institution and the District Director Ing. Ingrid Ortiz zone five. The objectives were developed with the application of interviews and polls that provided the information required for the analysis and interpretation of results, the current situation of the institution is analyzed for health and engi of the products they produce . In conclusion it was found that current managers of the bars of the Education Unit the Empalme lack knowledge about handling, nutrition, infrastructure and proper implementation, hygiene local and processes of food preparation making, it is a latent risk on the health of the educational community.